EFFECTIVENESS OF MUSYARAKAH MUTANAQISAH SCHEME IN IB MUAMALAT ASSET REFINANCING SYARIAH PRODUCTS - Anggun Permatasari, Linda; Kumalasari, Intan; Nuraini, Aulia; Puspaningsih, Nurul; Waluyo, Waluyo (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the effectiveness of the Musyarakah Mutanaqisah (MMQ) scheme in the iB Muamalat Asset Refinancing Syariah product at Bank Muamalat Indonesia. MMQ is a joint ownership contract with a gradually decreasing share, combining elements of musyarakah and ijarah as a Sharia-compliant alternative to conventional refinancing. The research employs a descriptive qualitative approach using a case study method, involving in-depth interviews, product document analysis, and literature review, including fatwas from the DSN-MUI and regulations from the OJK. The findings indicate that the implementation of MMQ complies with Sharia principles and applicable regulations. This scheme offers benefits to customers in the form of gradual asset ownership without interest, and provides profitability and payment certainty for the bank. However, operational challenges such as limited customer understanding, complex administrative procedures, and suboptimal digital systems need to be addressed. Enhancing public education, training for human resources, and strengthening technological infrastructure are necessary to support the sustainability and scalability of the MMQ product.